Patients with X-linked lymphoproliferative disease due to BIRC4 mutation have normal invariant natural killer T-cell populations - Marsh, Rebecca A (Clinical immunology (Orlando, Fla.), 2009)
Human invariant natural killer T cells (iNKT cells) are a unique population of T cells that express an invariantly rearranged T-cell receptor (TCR) composed of TCRValpha24 and TCRVbeta11 chains which recognize glycosphingolipid antigens presented by the CD1d molecule. iNKT cells are absent in patients with X-linked lymphoproliferative disease (XLP) due to SH2D1A mutation, and are reported to be decreased in patients with XLP due to BIRC4 mutations. However, mice deficient in the BIRC4 gene product, X-linked Inhibitor of Apoptosis (XIAP), have normal iNKT cell populations. Because of this, we studied iNKT cell populations in 6 patients with XLP due to BIRC4 mutations, with comparison to 103 pediatric and adult normal control samples. We found that iNKT cells constitute 0.008%-1.176% of normal peripheral blood T cells, and that iNKT cell populations were normal or increased in patients with BIRC4 mutations. We conclude that XLP due to BIRC4 mutation is not associated with decreased populations of iNKT cells, and that XIAP is likely not a requirement for iNKT cell development